The Proliferation of Weapons of Mass Destruction: The Iran Nuclear Deal - Saraki , Akeem Aderayo; Oladele, Femi Samuel (Kashere Journal of Politics and International Relations, 2025)
The proliferation of Weapons of Mass Destruction (WMDs) poses a significant threat to global peace and security, making it a critical area of focus in international relations. Employing theoretical framework and empirical review methods, this paper used Liberal Institutionalism (LI) and reviewed more than twelve (12) studies to examine four key objectives. The paper examined the role of international relations in curbing WMD proliferation, with a specific focus on the Iran Nuclear Deal, officially known as the Joint Comprehensive Plan of Action (JCPOA). The study also explored the multilateral negotiations that led to the JCPOA, emphasizing the intersection of diplomacy, power dynamics, and global governance in addressing WMD threats. It analyzed the successes and challenges of the agreement, of the JCPOA, with a particular focus on the consequences of the United States’ withdrawal under the Trump administration, which destabilized the agreement and reignited proliferation risks. Finally, the study underscored the importance of sustained international cooperation, robust institutional frameworks, and the delicate balance of incentives and enforcement in managing WMD proliferation. The findings contributed to the discourse on how international relations effectively address the proliferation of WMDs, providing lessons for future engagements in arms control and disarmament. It concluded by offering policy recommendations for strengthening global non-proliferation efforts, emphasizing the role of multilateral diplomacy, adaptive agreements, and the need to rebuild confidence among stakeholders.